PENGARUH PENGEMBANGAN KARIR, PELATIHAN KERJA, DAN KOMPENSASI TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BANGKALAN - Oktavina Kurnia Dewi; Sundjoto; Sri Rahayu (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the influence of career development, job training, and compensation on employee morale at work. The sample in this study were 79 employees at the Bangkalan Tax Service Office. The analytical tool used is multiple linear regression. The data processing application uses SPSS version 20. The results show that simultaneously the variables between career development, job training, and compensation affect employee morale, while partially the variables career development, job training, and compensation have a significant effect on employee morale at KPP Pratama Bangkalan